A cross-sectional study on the correlation between postnatal foot length and various other anthropometric parameters along with the gestational age - Dr. Abhinaya Arun Raj; Dr. K. Maheswari (Pediatric Review: International Journal of Pediatric Research, 2020)
Introduction: This study was done to assess the utility of foot length in determining the anthropometric parameters of a newborn in a tertiary care teaching hospital. Materials and Methods: This cross-sectional study among 270 newborns were done at Sri Venkateswaraa medical college hospital and research centre, from Nov 2018 to May 2020. All the healthy live newborns were taken into the study and newborns with congenital lower limb anomalies were excluded. Results: The mean birth weight of the neonate 2.948+0.344 kg which ranged from 2.050 kg to 3.750kg. The mean foot length, head circumference and chest circumference of the foot length was 8.113+0.468 cm, 48.989+1.093 cm, 34.437+0.659 cm and 32.372+0.734 cm respectively. The foot length had a maximum correlation with birth weight (r-value=0.905) followed by gestational age (r-value=0.809), length (r-value=0.786), head circumference (r-value=0.719) and chest circumference (r-value=0.603). Conclusion: Foot length had a significant correlation with birth weight and gestational age of the neonates. Foot length also correlated significantly with other anthropometric variables like length, head circumference and chest circumference.